DEMAND FOR FUEL WOOD AND ITS SUBSTITUTION POSSIBILITIES IN URBAN AREAS OF UMUAHIA METROPOLIS OF ABIA STATE - Iheke, Onwuchekwa; R., O.; Osuji, J. (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Fuel wood has grown in importance as a major source of energy for most households especially for cooking. An estimated 2.5 to 3.0 billion people rely on wood for fuel, both for warmth and food preparation. In Africa, wood is depended upon for up to 58% of all energy requirements and in many savanna areas, demand for fuel wood far exceeds the rate of growth. With the hike in price of other energy sources especially petroleum products due to partial withdrawal of subsidy and epileptic electricity and power outages, fuel wood demand and usage has been on the increase. The situation provides the rationale for this study. Specifically, the study analyzed pattern of fuel wood utilization, and substitution by the households, preference of energy source by the households, and determinants of demand for fuel wood. Purposive and random sampling technique was used in choosing the sample. The data collected using structured questionnaire and interview schedules were analyzed using descriptive statistical tools such as frequency tables, percentages and inferential statistical tools such as regression analysis. Results showed that the predominant use of fuel wood was for cooking, following by roasting and frying and that the major substitute for fuel wood was kerosene followed by cooking gas. The most preferred energy type by the households was cooking gas which was ranked first, followed by kerosene which was ranked second. The significant variable influencing the quantity of fuel wood demanded were gender, household size, income, years of education, price of fuel wood, and price of kerosene which is the major substitute for fuel wood. The own price elasticity was less than one, indicating that the demand for fuel wood was inelastic. There should be a revisit in the withdrawal of subsidy of kerosene and cooking gas used by the average Nigerian, in the face of rising inflation which reduces the purchasing power of households. This is so to ensure sustainability of forests from where this fuel wood are being harvested and avoid degradation of the environment. The Nigeria Government should hasten to invest in the development of cooking gas, as an alternative fuel source, instead of continuous flaring of this gas, which contributes to global warming.